FACTORS INFLUENCING THE CAPITAL STRUCTURE CHOICE OF KARACHI STOCK EXCHANGE (KSE100) - Ijaz Sanober; Dr. Lala Rukh; Irshad Ahmad; Rafiullah Khan; Irfan Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
This study explores the complex decision-making process related to capital structure among companies listed on the Karachi Stock Exchange 100 Index (KSE100). Its goal is to uncover the various factors that influence these important financial strategies within the context of Pakistan’s developing market. Using a comprehensive approach that combines quantitative econometric analysis with qualitative insights from interviews and case studies, the research sheds light on how firm-specific characteristics, market dynamics, corporate governance practices, and broader macroeconomic conditions interact. By grounding its analysis in the specific economic and regulatory environment of Pakistan, the study provides valuable perspectives on how both internal and external factors influence the capital structure decisions of companies operating in emerging economies. These insights go beyond traditional Western financial theories.